Hair growth potential of Salvia plebeia extract and its associated mechanisms - Guang-Ri Jin; Yi-Lin Zhang; Jonathan Yap; William A. Boisvert; Bog-Hieu Lee (Taylor & Francis Group, 2020)
Context Although Salvia plebeia (SP) R. Brown (Labiatae) is known to possess various biological activities, the effects of SP on hair growth have not been elucidated. Objective To investigate the hair growth potential of SP extract by using human dermal papilla cells (hDPCs) and C57BL/6 mice. Materials and methods The entire SP plant sample was ground into powder and extracted with 99.9% methyl alcohol. Various concentrations of SP extract were added to hDPCs to evaluate the proliferation, migration, and factors related to hair growth and cycling. Effect of topical SP administration on hair regrowth was tested in vivo in male C57BL/6 mice for 21 days. Results SP extract significantly increased the proliferation of cultured hDPCs at doses of 15.6 and 31.3 μg/mL compared to control group by 123% and 132%, respectively. Expression of hepatocyte growth factor increased while the level of TGF-β1 and SMAD2/3 decreased when treated with SP extract. At the molecular level, the extract activated Wnt/β-catenin signalling by raising β-catenin and phospho-GSK3β expression. SP extract also exerted anti-apoptotic and proliferative effects in hDPCs by increasing the Bcl-2/Bax ratio and activating cell proliferation-related proteins, ERK and Akt. Finally, the extract caused an induction of the anagen phase leading to significantly enhanced hair growth in treated male mice. Discussion and conclusion Our results indicate that SP extract has the capacity to activate hDPCs into a proliferative state to promote hair growth. Further research is necessary to determine the bioactive components and their mechanisms of action responsible for SP-related hair growth effect.